The influence of precision farming elements on the dynamics of the agro-chemical soil composition under irrigation - Alexey N. Tseplyaev; Sergey Ya. Semenenko; Andrey A. Kupriyanov; Elena A. Kuznetsova (Мелиорация и гидротехника, 2025)
Purpose: to study the layer-by-layer dynamics of mineral fertilizer nutrients when using precision farming elements in their combined local application with water-saturated hydrosorbents. Materials and methods. Experimental studies were conducted on the experimental field of the All-Russian Research Institute of Irrigated Agriculture. Generally accepted field research techniques were used. The pierced copolymers obtained artificially on the basis of sodium (Na) “Aquasorb” and potassium (K) “Aquasin”, the effect of local band application of hydrogel rates: 11.4; 14.8 and 18.2 g/running m, and the combined application of hydrogels in the same rates and “nitroammophoska” fertilizer at a rate of 33.5 g/running m, on the nutrient migration and potato yield were studied. Hydrogels and their mixture with mineral fertilizers were locally applied in bands with a specialized tool 0.08 m below the bottom of the potato planting furrow. The moisture regime of the 0.5 m soil layer was maintained at no less than 80 % of the minimum moisture capacity by irrigation at a rate of 300 m³/ha. The dynamics of nutrients was analyzed for the phases of potato development: planting, germination, budding, withering of tops and harvesting. Results. The content of nutrients in the root zone was found to be 1.27–1.47 times higher than in the control with the combined use of fertilizers and hydrogels. Analysis of the layered distribution of nutrients by depth indicates the phenomenon of nutrients “binding” by hydrogels in the increased moisture contour, the improved conditions and duration of mineral fertilizer dissolution, which affects the yield: when using a hydrogel enriched with fertilizers, it increased by 46.6 %, and the commercial potato tubers yield increased by 57.8 % compared to the control. Conclusions. Precision application of hydrogels improves the nutrient medium due to the deposition of nutrients in the root layer and ensures the increase in potato yield from 20.8 to 30.5 t/ha.